Schweitzer’s source of the contemporary idea of the sustainable development - Terlecka, Magdalena Klaudia (Studia Ecologiae et Bioethicae, 2010)
Sustainable development is the philosophy of economic development harmonized with the care of the natural environment. It enables one to combine the aspiration of the man to achieve high economic development combined with concern against the social and natural environment. One of precursors of the ecological thinking, according to contemporary principles of sustainable development was Albert Schweitzer. The author of the moral program-specific by the name Ethics for life, in which huge role-playing the responsibility, which is deciding on his humanity. This responsibility constitutes the philosophical base of the contemporary idea of sustainable development.